A Preliminary Investigation of Naturally Occurring Aluminum in Grains, Vegetables, and Fruits from Some Areas of China and Dietary Intake Assessment. Issue 3 (7th February 2019) - Liang, Jiang; Liang, Xuxia; Cao, Pei; Wang, Xiaodan; Gao, Peng; Ma, Ning; Li, Ning; Xu, Haibin
Abstract: An investigation of the naturally occurring aluminum contents in grains, fruits and vegetables locally planted in some areas of China was conducted, and the aluminum dietary intake from the investigated food was estimated. A total of 2, 469 samples were collected during 2013 to 2014 and tested for aluminum content using ICP‐MS method. The results showed that although 77.6% of the samples contained aluminum less than 5 mg/kg, significant variations of aluminum contents were observed in different food groups. Generally, the aluminum contents were found to be relatively high in dried grains and fresh vegetables, and low in fresh fruits. The mean value of aluminum contents in grains was 6.3 mg/kg, with wheat being the highest, followed by soybean and corn. The fresh vegetables had an average aluminum content of 4.7 mg/kg, with leafy vegetables being the highest, followed by bulb and stem vegetables. Most varieties of fresh fruits were low in aluminum, with the mean of 1.3 mg/kg. Based on the food consumption data from the China National Nutrient and Health Survey, the average weekly dietary intake of naturally occurring aluminum from the investigated foods was estimated to be 0.62 mg/kg bw for the general population and 0.55 to 1.00 mg/kg bw for different age groups. Grains and vegetables were the main contributors to the overall intake. Evaluated against the provisional tolerable weekly intake (PTWI) of 2 mg/kg bw, the dietary naturally occurring aluminum intake from the investigated foods was considered to be no safety concern.